2021
DOI: 10.1021/acscatal.1c00811
|View full text |Cite
|
Sign up to set email alerts
|

To Rebound or...Rebound? Evidence for the “Alternative Rebound” Mechanism in C–H Oxidations by the Systems Nonheme Mn Complex/H2O2/Carboxylic Acid

Abstract: In this work, it has been shown that aliphatic C−H oxidations by bioinspired catalyst systems Mn aminopyridine complex/H 2 O 2 /carboxylic acid in acetonitrile afford predominantly a mixture of the corresponding alcohol and the ester. The alcohol/ ester ratio is higher for catalysts bearing electron-donating groups at the aminopyridine core. Isotopic labeling studies witness that the oxygen atom of the alcohol originates from the H 2 O 2 molecule, while the ester oxygen comes exclusively from the acid. Oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…An analogous competition has been recently proposed by Bryliakov and co-workers in the benzylic C−H bond oxygenation of cumene with H 2 O 2 catalyzed by manganese complexes. 26 In this study, the hydroxylation/esterification product ratio was observed to be unaffected by the carboxylic acid loading, increasing increasing steric bulk of the carboxylic acid additive, supporting the involvement of competitive hydroxyl and carboxylate rebound pathways in these reactions.…”
Section: ■ Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…An analogous competition has been recently proposed by Bryliakov and co-workers in the benzylic C−H bond oxygenation of cumene with H 2 O 2 catalyzed by manganese complexes. 26 In this study, the hydroxylation/esterification product ratio was observed to be unaffected by the carboxylic acid loading, increasing increasing steric bulk of the carboxylic acid additive, supporting the involvement of competitive hydroxyl and carboxylate rebound pathways in these reactions.…”
Section: ■ Discussionsupporting
confidence: 62%
“…Within this mechanistic picture, the steric hindrance of the carboxylic acid additive plays a crucial role in determining the contribution of the carboxylate rebound pathway, with the relative importance of this pathway, quantified by the P1-O / P1a-OX n ratio, that decreases with increasing steric bulk of the acid, being completely suppressed when employing the very bulky Phth-Tle-OH (Scheme a). An analogous competition has been recently proposed by Bryliakov and co-workers in the benzylic C–H bond oxygenation of cumene with H 2 O 2 catalyzed by manganese complexes . In this study, the hydroxylation/esterification product ratio was observed to be unaffected by the carboxylic acid loading, increasing with increasing steric bulk of the carboxylic acid additive, supporting the involvement of competitive hydroxyl and carboxylate rebound pathways in these reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once formed, IM10 might evolve along the three potential branches: , OH-rebound, AcO-rebound, and desaturation. The OH-rebound branch involves the recombination of two fragments in IM10 , leading to the hydroxylation product complex IM11 , which then dissociates into the hydroxylated heterocycle intermediate IM12 and the Mn III –OAc species.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, DFT calculations have been performed at the B3LYP/def2‐TZVPP (for Fe)/6‐311G(d) (for other atoms) level of theory (see Supporting Information for details), which approach has been recently shown to adequately predict the gaps between different spin states of transition metal oxo species [12a,b] . Crucially, the results witness that the difference between the energies of the high‐ and low‐spin isomers decreases with increasing electron‐donating properties of the substituents (H, OMe, NMe 2 ), such that high‐spin structures become preferred in the case of very strong electron donors NMe 2 (Table 2).…”
Section: Discovery Of the First Oxoiron(v) Intermediatesmentioning
confidence: 99%